Jing Ke ci Qin wang = The emperor and the assassin [videorecording (DVD)] - Chen, Kaige, 1952-; Chen, Kaige, 1952-; Chen, Kaige, 1952-; Chen, Kaige, 1952-; Wang, Peigong; Kao, Shirley; Iseki, Satoru, 1943-; Gong, Li, 1965-; Zhang, Fengyi; Li, Xuejian, 1954-; Sun, Zhou; Lü, Xiaohe, 1945-; et al. (SONY Pictures classics., 2000)
"Ying Zheng, the King of Qin, has one driving ambition: to unify China's seven kingdoms into one magnificent empire. Impressed by her lover's convictions, Lady Zhao helps Ying Zheng concoct an assassination plot that would justify the conquest of Qin's most powerful enemy"--Container